PENYULUHAN PEMANFAATAN LIMBAH ORGANIK SEBAGAI BAHAN AMELIORAN UNTUK MENINGKATKAN PRODUKTIVITAS JAGUNG KETAN DI MUNCUK KARYA, AMPENAN - Astiko, Wahyu; Fauzi, Mohamad Taufik; Sudirman, Sudirman; Muthahanas, Irwan (Universitas Mataram, 2024)
Glutinous corn is popular due to its delicious taste, savory flavor, and soft texture, with a very high amylopectin content of up to 90%, which is beneficial for diabetics. Its popularity is increasing as an alternative food, such as corn porridge and instant corn rice. However, the productivity of glutinous corn in the